2018
DOI: 10.1016/j.eneco.2018.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Renewable energy, oil prices, and economic activity: A Granger-causality in quantiles analysis

Abstract: This paper analyzes the causal relationship between renewable energy consumption, oil prices, and economic activity in the United States from July 1989 to July 2016, considering all quantiles of the distribution. Although the concept of Granger-causality is defined for the conditional distribution, the majority of papers have tested Granger-causality using conditional mean regression models in which the causal relations are linear. We apply a Granger-causality in quantiles analysis that evaluates causal relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
123
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 324 publications
(134 citation statements)
references
References 140 publications
11
123
0
Order By: Relevance
“…Further, a 1% acceleration in tourism growth increases the economic growth of IEA countries by 34% in model I, while it decreases the EFP of IEA countries by 24% in model II. We found that both energy consumption and tourism growth are significant factors in the economic growth of IEA countries, a result that agrees with those of Adams et al ( 2018 ), Aydin ( 2019 ), Belaïd and Zrelli ( 2019b ), Mohamed et al ( 2019 ), Rahman and Velayutham ( 2020 ), Troster et al ( 2018 ), Vural ( 2020 ), and Zafar et al ( 2019 ). All these studies showed that energy consumption is compatible with economic growth.…”
Section: Resultssupporting
confidence: 90%
“…Further, a 1% acceleration in tourism growth increases the economic growth of IEA countries by 34% in model I, while it decreases the EFP of IEA countries by 24% in model II. We found that both energy consumption and tourism growth are significant factors in the economic growth of IEA countries, a result that agrees with those of Adams et al ( 2018 ), Aydin ( 2019 ), Belaïd and Zrelli ( 2019b ), Mohamed et al ( 2019 ), Rahman and Velayutham ( 2020 ), Troster et al ( 2018 ), Vural ( 2020 ), and Zafar et al ( 2019 ). All these studies showed that energy consumption is compatible with economic growth.…”
Section: Resultssupporting
confidence: 90%
“…The first strategy was to increase the share of oil supplied by OPEC, thereby reducing the price of oil, while the second strategy was to allow high-cost competitors to remain in the market and the result of the study was that when efficient members who are non OPEC members are more attractive to OPEC when they are not high in renewable energy production, consumers view both commodities as homogeneous products, in addition to that the pressure strategy stimulates more renewable energy production when the cost is low, and finally if non-OPEC countries can influence the price, the pressure strategy arises in light of Less demanding conditions when renewable energy is present. Another study by Troster, Victor and others [8] concluded that, the study has a causal relationship between renewable energy consumption, oil prices, and economic activity in USA from June 1989 to July 2016. The study found that there is a two-way causality between changes in renewable energy consumption and economic growth at the lowest quantities for distribution.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The most relevant advantages for our purposes are that it enables nonlinear quantile-regression specifications, it has good finite-sample power, and it is robust to nonnormality in the data. The following section follows closely the explanation of Granger causality in quantiles from Troster (2018) and Troster et al (2018). The reader is asked to consult these references for a detailed explanation of the methodology.…”
Section: Linear and Nonlinear Granger-causality Testsmentioning
confidence: 99%